Paracrine Signaling through the JAK/STAT Pathway Activates Invasive Behavior of Ovarian Epithelial Cells in Drosophila. - Silver, D.L.; Montell, D.J. (Cell, 2001)
The JAK/STAT signaling pathway, renowned for its effects on cell proliferation and survival, is constitutively active in various human cancers, including ovarian. We have found that JAK and STAT are required to convert the border cells in the Drosophila ovary from stationary, epithelial cells to migratory, invasive cells. The ligand for this pathway, Unpaired (UPD), is expressed by two central cells within the migratory cell cluster. Mutations in upd or jak cause defects in migration and a reduction in the number of cells recruited to the cluster. Ectopic expression of either UPD or JAK is sufficient to induce extra epithelial cells to migrate. Thus, a localized signal activates the JAK/STAT pathway in neighboring epithelial cells, causing them to become invasive.